Pemanfaatan Lumpur Limbah Tinta Sebagai Bahan Substitusi Pada Material Bangunan Berbasis Semen - Arif Hidayat (MEDIA KOMUNIKASI TEKNIK SIPIL, 2012)
Ink residue as a site product from printing factories can accumulate in time forming an environmental threatening product. Beside from its magnitude in terms of quantity, its black-brownish color can also contaminate surrounding areas. Studies performed at the Material and Structural Laboratory, Diponegoro University, attempt to increase this ink residue’s commercial value by using it as a substituting material for cement based products. Cement based products which are investigated are concrete and paving blocks. Concrete is a building material consisting of sand, gravel and cement acting as binding agent. On the other hand Paving Blocks consisting only of sand and cement and are formed by pressing the mass, requiring a mix with a very low water content. The ink residue was replacing parts of the sand.  Factors being observed are the compression strength, weight and unit price. Keywords: ink residue, concrete, paving blocks, compression and unit weightPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3930[How to cite: Hidayat, A., 2006, Pemanfaatan Lumpur Limbah Tinta sebagai Bahan Substitusi pada Material Bangunan Berbasis Semen, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 13-20]